Re-Engineering the Importance of French Language to Diplomatic Practices and International Relations (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study examined the, relevance and connection of the French language to the practice of diplomacy and international relations. It has been argued severally that French Language seems not only an instrument of communication but part of the very essence of diplomacy. The reason for this assertion is not far-fetched; it was adduced that diplomats engage in negotiations, persuasion, presentation and communications, all of which necessitates language skills for the effective conduct of diplomatic works. French Language is one of the languages that is used to achieve the vital needs in diplomacy, likewise its antecedents in the world of diplomacy in the past and present day. Therefore, this study essentially argues that the French language remains relevant for the conduct of the relations generally and the necessity of its study by the students of Arts and Language Education, Language and Literary Studies and History and International Studies. Some of the major points highlighted in this work include origin of French language and its growth; History of Diplomacy and International Relations - Growth and Relevance; The Relevance and Interconnectedness of the Language and Diplomatic Practices and the Relevance of the Study of the French language to students of International Relations. In conclusion, the use of French laid emphasises on how beneficial it is to foster understanding and cooperation in this international community. The work further recommended that it is necessary for students to learn and understand French language so that they can function well in the global world.